THE JUDGE CONSIDERATIONS IN MAKING DECISION AGAINST NARCOTICS IN CHILDREN - Faridah, Idah; Kunarso, Kunarso (jfpublisher, 2022)
The narcotics abuse in Indonesia is closely related to narcotics users who obtain it from illicit trafficking that caused by drug attacks in Indonesia that reached the point of endangering the nation life and security. The Indonesian Child Protection Commission (KPAI) noted that 5.9 million children from 87 million child population in Indonesia are became drug addicts. This research aims to find out how the application of criminal law to children as perpetrators of drug abuse and how the juridical analysis based on judge's considerations in making criminal decisions for children as perpetrators of narcotics crimes. This research uses normative legal research that confines itself to the study of the law as an object and excludes any non-legal information from discussed problem. This research shows that when a child commits a crime within the specified age limit, it is a legal obligation for law enforcement officials to conduct special procedural law for children, and it is prohibited to apply general procedural law. However, if a child commits a crime beyond their age limit, the law enforcement officials has an authority to implement the general procedural law.